2012
DOI: 10.1038/nm.2791
|View full text |Cite
|
Sign up to set email alerts
|

Viral delivery of miR-196a ameliorates the SBMA phenotype via the silencing of CELF2

Abstract: Spinal and bulbar muscular atrophy (SBMA) is an inherited neurodegenerative disorder caused by the expansion of the polyglutamine (polyQ) tract of the androgen receptor (AR-polyQ). Characteristics of SBMA include proximal muscular atrophy, weakness, contraction fasciculation and bulbar involvement. MicroRNAs (miRNAs) are a diverse class of highly conserved small RNA molecules that function as crucial regulators of gene expression in animals and plants. Recent functional studies have shown the potent activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 35 publications
3
117
0
Order By: Relevance
“…With a clinical setting in mind, experiments were done in human patient fibroblasts. miR-196a overexpression in an SBMA mouse model significantly downregulated both CELF2 and AR mRNA levels, improving SBMA phenotypes, suggesting miR-196a-mediated treatment as a potential clinical therapy for SBMA patients [141].…”
Section: Spinobulbar Muscular Atrophymentioning
confidence: 94%
See 1 more Smart Citation
“…With a clinical setting in mind, experiments were done in human patient fibroblasts. miR-196a overexpression in an SBMA mouse model significantly downregulated both CELF2 and AR mRNA levels, improving SBMA phenotypes, suggesting miR-196a-mediated treatment as a potential clinical therapy for SBMA patients [141].…”
Section: Spinobulbar Muscular Atrophymentioning
confidence: 94%
“…Recently, Miyazaki et al [141] demonstrated a potential SBMA therapy using a novel approach exploiting the miRNA pathway. They identified miR-196a expression as significantly upregulated in the spinal cord of transgenic mice at advanced disease stages.…”
Section: Spinobulbar Muscular Atrophymentioning
confidence: 99%
“…It has been demonstrated that they can significantly improve the phenotype of SBMA mice but has never been tested in human patients [78].…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…Two major approaches have been tested to deliver miR-mimics: (I) miR-mimic viral based overexpression ( Figure 1C) and (II) injection (intravenously or directly into the affected tissue) of miR-mimics that are linked to liposomal nanoparticles, atelocollagen or polyethyleneimine (81)(82)(83) (Figure 1C). Systemically viral based overexpression of a miR-mimic can be performed by using adeno-associated viruses (AAVs) (84,85) (Figure 1C). Due to the natural tropism of AAVs to cell types, receptors or organs, a cardiac-specific expression of the miR-mimicking constructs could also be realized (86).…”
Section: Mir Mimicsmentioning
confidence: 99%